Getting Engaged: Resources to Support Community Engagement Practices - Kathryn A. Stofer (EDIS)
This document is part of the Getting Engaged series, which is designed to help Extension and research faculty and other community engagement professionals improve their engagement with a variety of stakeholder audiences. This 4-page document offers resources for practitioners at all stages, from those just beginning to think about engagement to those who have been engaging their communities for years. Written by Kathryn A. Stofer and published by the Department of Agricultural Education and Communication, February 2017.